2022
DOI: 10.3390/jmse10010062
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Single-Particle Motion Using CFD-DEM in Varying-Curvature Elbows

Abstract: Centrifugal pumps are the critical components in deep-sea mining. In order to investigate the particle motion in the curved channel of the impeller, three different types of curvature conform to blade profile to simplify the impeller design of pumps. A numerical study is conducted to investigate the flow field in a varying-curvature channel for solid-liquid two-phase flow. The flow of particles within the varying curvature channel is studied by combining the discrete element method (DEM) with computational flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was found by Wang [49] et al that the particle size mainly affects the vortex strength in the pump, and has a limited impact on the hydraulic performance after the calculation and analysis of the solid-liquid two-phase unsteady flow of a single-stage deep-sea mining lifting pump based on CFD-DEM. Ning [50] analyzed and compared the CFD-DEM calculation results with the particle velocity test results (Particle Image Velocimetry (PIV)), and when the grid was dense enough, the simulation results were very close to the experiments, which fully verified that CFD-DEM was effective in simulating particles Accuracy and reliability of kinetics. Deng [27] artificial particle distribution, particle dynamics, and slurry hydraulic performance through CFD-DEM, and compared the experiment, and found that the error of CFD-DEM coupling simulation of slurry hydraulic performance can be controlled within 2%.…”
Section: Current Status Of Simulation Research On Solid-liquid Two-ph...mentioning
confidence: 73%
“…It was found by Wang [49] et al that the particle size mainly affects the vortex strength in the pump, and has a limited impact on the hydraulic performance after the calculation and analysis of the solid-liquid two-phase unsteady flow of a single-stage deep-sea mining lifting pump based on CFD-DEM. Ning [50] analyzed and compared the CFD-DEM calculation results with the particle velocity test results (Particle Image Velocimetry (PIV)), and when the grid was dense enough, the simulation results were very close to the experiments, which fully verified that CFD-DEM was effective in simulating particles Accuracy and reliability of kinetics. Deng [27] artificial particle distribution, particle dynamics, and slurry hydraulic performance through CFD-DEM, and compared the experiment, and found that the error of CFD-DEM coupling simulation of slurry hydraulic performance can be controlled within 2%.…”
Section: Current Status Of Simulation Research On Solid-liquid Two-ph...mentioning
confidence: 73%